Physiological significance of the microclimate in night refuges of the numbat Myrmecobius Fasciatus - Cooper, Christine; Withers, P. (2005)
Numbats (Myrmecobius fasciatus) seek overnight refuge in hollow logs, tree hollows and burrows, which provide protection from predators. Occupied night refuges were on average 5ºC warmer than ambient temperature, which would result in considerable energy savings (35 kJ over 12 h). Use of a nest within the refuge reduced calculated energy expenditure by a further 55 kJ over 12 h. Mean nightly temperature didn’t differ with refuge type, but the nightly pattern of refuge temperature did. Burrows had higher insulation than logs or tree hollows, and had more constant night temperatures and higher minimum temperatures. Season had a significant influence on refuge temperature, with lower temperatures in winter than in other seasons for all refuge types. The gas composition of occupied night refuges was different to ambient, with refuge air differing in O2 content by a maximum of 2.3%, and CO2 by no more than 3.0% from ambient levels. The relative humidity in M. fasciatus refuges was extremely variable (23- 100%), but was generally lower than ambient relative humidity. The overnight refuges of M. fasciatus (hollow logs, tree hollows and burrows) significantly buffer thermal conditions without major effects on the gaseous or hygric environment.